Chain Procedure and Structuring of a Subject - Bhattacharyya, G. (Journal of Information and Knowledge, 1972)
The theoretical foundation of the Chain Procedure is discussed. Its intimate relationship with the postulates about the structures of names-of-subject is shown. The application of these postulates for semantic cum syntactic analysis of names-of-subject is demonstrated. The problems of subject headings are enumerated. The term 4 Chain Procedure is defined. The variables that contribute to the development of the different versions of the Chain Procedure are distinguished. The different versions of the Chain Procedure are illustrated. The contributions on the Chain Procedure since 1934 are reviewed to show the different stages of its development.